2008
DOI: 10.1002/cjg2.1198
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐quantitative Analysis of Factors Affecting Gas Hydrate Formation Conditions and Its Fractions

Abstract: Gas hydrate formation conditions and its fraction out of pore space are two important issues. Based on the theoretical thermo‐dynamic model of gas hydrate formation and accumulation, the semi‐quantitative analysis on various intrinsic factors (such as temperature, pressure, gas composition, pore‐water salinity, sediment pore size) is conducted to characterize their effects on gas hydrate formation conditions and its fraction out of pore space. The analytical results indicate that gas composition plays a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Moreover, it was verified via the simulation of hydrate formation and decomposition that under the same temperature and pressure conditions, heavier gas molecules are more prone to turn into hydrates with a higher thermal stability than pure methane. 3 , 4 , 50 This agrees with the simulation and calculation results in this study. It was found that pure methane HSZs cannot form under a geothermal gradient of 2.3 °C/100 m and a permafrost thickness of 86 m. However, a HSZ with a thickness of 735 m can be found at a depth of 115–850 m when wet gas is present with a dryness coefficient of 0.88.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it was verified via the simulation of hydrate formation and decomposition that under the same temperature and pressure conditions, heavier gas molecules are more prone to turn into hydrates with a higher thermal stability than pure methane. 3 , 4 , 50 This agrees with the simulation and calculation results in this study. It was found that pure methane HSZs cannot form under a geothermal gradient of 2.3 °C/100 m and a permafrost thickness of 86 m. However, a HSZ with a thickness of 735 m can be found at a depth of 115–850 m when wet gas is present with a dryness coefficient of 0.88.…”
Section: Discussionsupporting
confidence: 92%
“…Actually differences in gas composition inevitably exist between the Qaidam basin, the Tarim basin and the QHPP; thus the gas composition of their referred gas fields can not be fully representative of the study area. More over, the hydrocarbon gas composition is not only an important factor affecting gas hydrate formation conditions besides temperature and pressure, but it is also a decisive element for gas hydrate content [25] .…”
Section: Introductionmentioning
confidence: 99%
“…have various effect on gas hydrate stability zone. Quantitative-semi quantitative modeling results show that gas composition, especially the entry of propane has a maximal effect on gas hydrate stability zone [19] .…”
Section: Discussionmentioning
confidence: 98%
“…If the thermal gradient does not change, the depth of permafrost base is closely related to the top surface temperature of permafrost and they have a negative correlation. Theoretical calculation [19] shows that gas hydrate formation conditions are more sensitive to temperature than pressure (the depth of permafrost base); for 1 • C increment in temperature, the increment in pressure required for gas hydrate formation will be about 700 kPa (approximately 7 atmospheric pressures or 70 m of permafrost thickness in hydrostatic pressure). Namely when thermal gradient within the permafrost keeps constant the interval of gas hydrate occurrence is determined by permafrost thickness.…”
Section: Discussionmentioning
confidence: 99%